2018
DOI: 10.1371/journal.pone.0200411
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in the diversity and structure of faunal assemblages associated with kelp holdfasts (Laminaria hyperborea) in the northeast Atlantic

Abstract: Kelp species are ecologically-important habitat-formers in coastal marine ecosystems, where they alter environmental conditions and promote local biodiversity by providing complex biogenic habitat for an array of associated organisms. While it is widely accepted that kelps harbour significant biodiversity, our current understanding of spatiotemporal variability in kelp-associated assemblages and the key environmental drivers of variability patterns remains limited. Here we examined the influence of ocean tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 118 publications
7
27
0
Order By: Relevance
“…For instance, kelp forests dominated by the warm‐temperate species will still exhibit high rates of carbon capture, as plant primary production—and therefore carbon assimilation—was higher than that of the cool‐water kelp. Both species are also morphologically similar and form canopies of similar heights and plant densities (Smale et al., ; Supporting Information Table ) and, as such, kelp forests dominated by the range‐expanding species are likely to continue to provide habitat for fish, invertebrate, and algal species (O'Brien, Mello, Litterer, & Dijkstra, ; Teagle, Moore, Jenkins, & Smale, ). That said, recent work has shown that the epibiotic assemblages associated with kelp stipes, which are typically dominated by red seaweeds and sessile invertebrates, are less diverse in the warm‐temperate species (Teagle & Smale, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, kelp forests dominated by the warm‐temperate species will still exhibit high rates of carbon capture, as plant primary production—and therefore carbon assimilation—was higher than that of the cool‐water kelp. Both species are also morphologically similar and form canopies of similar heights and plant densities (Smale et al., ; Supporting Information Table ) and, as such, kelp forests dominated by the range‐expanding species are likely to continue to provide habitat for fish, invertebrate, and algal species (O'Brien, Mello, Litterer, & Dijkstra, ; Teagle, Moore, Jenkins, & Smale, ). That said, recent work has shown that the epibiotic assemblages associated with kelp stipes, which are typically dominated by red seaweeds and sessile invertebrates, are less diverse in the warm‐temperate species (Teagle & Smale, ).…”
Section: Discussionmentioning
confidence: 99%
“…The large kelp Laminaria hyperborea functions as the dominant foundation species along much of the wave-exposed rocky coastline of the northeast Atlantic 15 17 , where it forms extensive kelp forest habitat 18 , 19 , supports high levels of biodiversity 20 and stores and releases vast amounts of organic matter 21 , 22 . Despite the critical importance of L. hyperborea and the kelp forest habitats it creates in the northeast Atlantic, several important knowledge gaps pertaining to its biology and ecology still persist, including reliable estimates of NPP from multiple populations and across large spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…In the NE Atlantic, shallow subtidal reefs, fully or partially exposed to wave action, are dominated by the large stipitate kelp Laminaria hyperborea (Smale, Burrows, Moore, O'Connor, & Hawkins, 2013;Steneck et al, 2002;Teagle et al, 2017). Individual "plants" support diverse assemblages of epiphytic algae and associated invertebrates on their stipes, as well as rich invertebrate assemblages within their holdfasts (Christie et al, 2003;Moore, 1973;Teagle et al, 2017Teagle et al, , 2018. Beneath these, extensive kelp stands lie functionally diverse and structurally complex assemblages of understory algae, ranging from simple foliose species to more complex calcareous algae and corticated macrophytes (Leclerc et al, 2016;Maggs, 1986).…”
Section: Introductionmentioning
confidence: 99%